Decoupled approach to integrated optimum design of structures and robust control systems - Bozca, Mehmet; Mugan, Ata; Temeltas, Hakan (SPRINGER, 2008)
Integrated optimum design of structures and control systems is studied by using H-2 and H-infinity robust control formulations. It is derived that conventional simultaneous optimization approach by using these robust control laws can be approximated by a decoupled optimization approach in which the structures are optimized by shaping the structural singular values and then the controllers can be designed, namely, decoupled, sequential or successive design approach. It is shown that the proposed decoupled optimization approach can be used to design optimum robust structures and has certain advantages over the conventional simultaneous optimization procedures such as it avoids the drawbacks of pure robust control laws and faster, especially if the number of degrees of freedom (DOF) of the associated structure is large. The bounds for achievable robustness measures are also obtained. Following, simultaneous and decoupled optimization approaches are applied to active control of two structures. The optimization results are presented, and it is concluded that the proposed decoupled optimization approach yields the achieved global minimum much faster than the simultaneous optimization approach.
Keywords: structural optimization; robust control; singular value decomposition; finite element methods; integrated/concurrent/simultaneous optimum design; COMPONENT MODE SYNTHESIS; SIMULTANEOUS-OPTIMIZATION; SENSITIVITY; COMPENSATION; Computer Science; Engineering; Mechanics